Perbandingan Motivasi Intrinsik dan Ekstrinsik Terhadap Partisipasi Siswa dalam Pembelajaran Atletik pada Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan - Alang Surya Maulana; Carsiwan; Sufyar Mudjianto (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aimed to determine the effects of intrinsic and extrinsic motivation on students' participation in athletics learning and to compare which type of motivation has a more dominant influence on students' participation. The study employed a quantitative approach using an ex post facto research design. The population consisted of Grade XI students at SMA Negeri 8 Bandung, with a sample of 230 students selected using the Slovin formula and proportionate stratified random sampling technique. Data were collected through questionnaires adapted from the Intrinsic Motivation Inventory (IMI), Valence, Instrumentality, Expectancy Motivation Scale (VIEMS), and Student Engagement in School Items (SESI). The data were analyzed using IBM SPSS through descriptive statistical analysis, normality testing, linearity testing, multicollinearity testing, and simple linear regression analysis. The results indicated that intrinsic motivation had a positive and significant effect on students' participation (β = 0.706, p < 0.05), while extrinsic motivation also had a positive and significant effect on students' participation (β = 0.762, p < 0.05). A comparison of the standardized beta coefficients showed that extrinsic motivation had a more dominant influence on students' participation in athletics learning than intrinsic motivation. In conclusion, both intrinsic and extrinsic motivation significantly and positively influenced students' participation; however, extrinsic motivation was the more dominant factor. Therefore, efforts to increase students' participation should focus on strengthening intrinsic motivation while optimizing extrinsic factors, such as providing constructive feedback, appropriate rewards, and a supportive learning environment. Keywords: Intrinsic Motivation, Extrinsic Motivation, Student Participation, Athletics Learning, Physical Education